2010
DOI: 10.1111/j.1553-2712.2010.00916.x
|View full text |Cite
|
Sign up to set email alerts
|

Serum Ischemia‐modified Albumin Levels in an Experimental Acute Mesenteric Ischemia Model

Abstract: Objectives: This experimental study aimed to assess the changes in the levels of serum ischemiamodified albumin (IMA) and interleukin-6 (IL-6) by time in cases of acute mesenteric ischemia due to superior mesenteric artery occlusion.Methods: Twenty-one New Zealand rabbits were randomly divided into three groups. Blood samples were collected at hours 0, 1, 3, and 6 from animals in a control group; a sham group following a simple laparotomy; and in an ischemia group following superior mesenteric artery ligation.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
27
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(32 citation statements)
references
References 25 publications
4
27
1
Order By: Relevance
“…Dundar et al 18 reported a rabbit model of mesenteric ischemia and found that significantly higher serum IMA levels were present both in the control group and in the mesenteric ischemia group (means of 0.451 to 0.720 ABSU). Unluer et al 19 also reported high serum IMA levels for time variable different ischemia groups in another rabbit model (means of 0.60 to 0.65 ABSU).…”
mentioning
confidence: 99%
“…Dundar et al 18 reported a rabbit model of mesenteric ischemia and found that significantly higher serum IMA levels were present both in the control group and in the mesenteric ischemia group (means of 0.451 to 0.720 ABSU). Unluer et al 19 also reported high serum IMA levels for time variable different ischemia groups in another rabbit model (means of 0.60 to 0.65 ABSU).…”
mentioning
confidence: 99%
“…35,[39][40][41] In this study, significant morphological changes were observed in both the IG and the I/RG groups. In the ischemic group, the degree of mucosal injury was minimal to moderate,…”
Section: Discussionmentioning
confidence: 99%
“…IMA increases in myocardial ischemia, cancers, infections, end-stage renal disease, liver disease, and cerebral ischemia (2)(3)(4)(5)(6)(7)(8)(9)(10)16). This study shows that serum IMA levels increase even in the absence of hypoxia markers in patients undergoing GTC seizures and that serum IMA values are directly proportional to length of seizure.…”
Section: Discussionmentioning
confidence: 99%
“…The ACB test is a quantitative assay that measures IMA in human serum (2). Experimental and clinical studies have shown an increase in IMA levels in blood in various organ ischemias or injuries, particularly myocardial ischemia, and systemic ischemias (2)(3)(4)(5)(6)(7)(8)(9). One study of patients with PCI reported that IMA is not only a marker of the occurrence of an ischemic event, but also an indicator of the severity of ischemia (10).…”
Section: Introductionmentioning
confidence: 99%